Correspondence of Arabic Loanouts in Ibrat's Works to the Primary Source - Amonov Mukhtorjon Umarovich; Jonbo'taeva Zumradkhan (Zien Journals, 2023)
The article analyzes the question of the compatibility of Arabic adaptations with the original in the works of Ishaq Khan and Ibrat. Borrowed words in "History of Ferghana" were lexically-semantically analyzed.
Keywords: History of Fergana; appropriation; Arabic suffix